Efficacy and safety of ribavirin plus pegylated interferon alfa in geriatric patients with chronic hepatitis C. Issue 1 (5th November 2012) - Hu, C.‐C.; Lin, C.‐L.; Kuo, Y.‐L.; Chien, C.‐H.; Chen, S.‐W.; Yen, C.‐L.; Lin, C.‐Y.; Chien, R.‐N.
Summary Background Limited data are available on the efficacy and safety of antiviral therapy in geriatric patients with chronic hepatitis C virus (HCV) infection. Aim To evaluate the efficacy and safety of pegylated interferon (pegIFN) plus ribavirin (RBV) therapy in geriatric HCV‐infected patients. Methods Ninety‐one geriatric patients (age ≥65 years; the elderly group) with HCV infection and 91 gender‐ and HCV genotype‐matched middle‐aged patients (age 50–64 years; the younger group) were assigned to receive weekly pegIFN injection plus weight‐based oral RBV for 24 weeks. The on‐ and off‐treatment virological responses were evaluated for treatment efficacy. Results In intention‐to‐treat analysis, the sustained virological response (SVR) rate was substantially decreased in the elderly patients (elderly group vs. younger group, 40.7% vs. 61.5%, respectively; P = 0.005). The SVR rate was significantly lower in geriatric patients than in middle‐aged patients with HCV genotype non‐1 (54.3% vs. 82.9%; P = 0.01), but the difference was not significant with HCV genotype 1 (32.1% vs. 48.2%; P = 0.083). Furthermore, the older patients infected with HCV genotype non‐1 who achieved a rapid virological response had a similar SVR rate to that of the younger patients. The withdrawal rate was 13.2% in the elderly group and 7.7% in the younger group. Conclusions Compared with middle‐aged patients, the therapeutic efficacy of pegylated interferon plus ribavirin therapy is lower in hepatitis C virus‐infected geriatric patients with an acceptable withdrawal rate. Considering prolonged lifespan in geriatric patients, we recommend treating geriatric hepatitis C virus‐infected patients who have significant hepatic fibrosis and no other health problems.